ANALISIS LABA KOTOR: KINERJA LABA KOTOR BANK BCA DALAM KONTEKS PERBANKAN DI INDONESIA - Nadila Salsavira; Aulia Daisy Arsy Syafitri; Sonia Br Ginting; Renny Oktafia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Gross profit analysis is an important method in evaluating the financial performance of a financial institution, including banks. In the context of Indonesian banking, Bank BCA (Bank Central Asia) is one of the leading banks that plays a significant role in the economy. This research aims to analyze the gross profit performance of Bank BCA and evaluate its relative position in the Indonesian banking industry. The method of gross profit analysis involves calculating gross income and operational costs to measure the efficiency and profitability of the bank. The research results indicate that Bank BCA's gross profit has experienced stable growth over the past few years, reflecting strong performance in generating income and managing operational costs. Factors such as product innovation, network expansion, and effective risk management strategies have contributed to this achievement. Additionally, Bank BCA has maintained a competitive position in the Indonesian banking industry, with relatively high gross profits compared to its competitors. However, challenges remain in facing market dynamics and evolving regulations. Therefore, Bank BCA needs to continue evaluating and making strategic adjustments to ensure operational sustainability and sustainable growth in the future. This research provides valuable insights for stakeholders in the banking industry, regulators, and investors in understanding the performance and position of Bank BCA in the Indonesian banking ecosystem.